PROTOTYPE OF HOME SECURITY MONITORING SYSTEM BASED ON INTERNET OF THINGS - Wijaksana, Wibi Wijaksana; Budiyanto , Setiyo; Fajar Banardi, Deswandi; Medriavin Silalahi, Lukman (Metrik Serial Humaniora dan Sains, 2024)
Nowadays, the criminality rate that is troubling demands home security to become a smart home, which is a problem in this research. The purpose of this research is to design a home door security system using a magnetic switch door MC-38 to detect the condition of the door in an open or closed condition and the front and side areas of the house using a PIR HC-SR501 sensor to detect the movement of an object. Sensor data is processed by WeMos D1 Mini connected to WiFi and the data is forwarded to the MQTT Explorer server where the information can be accessed by users through an application installed on a smartphone. The results showed that the HC-SR501 PIR sensor successfully detected human movement with a distance of 5m and an average notification sending time of 2.99 seconds, then the MC-38 sensor on the front and side doors of the house had an average notification time of 1.98 seconds.